Pseudomonas aeruginosa type III secretion system virulotypes and their association with clinical features of cystic fibrosis patients - Sarges, Edilene do Socorro Nascimento Falc?o (Dove Medical Press, 2020)
Purpose: Pseudomonas aeruginosa appears as the main pathogen in cystic fibrosis (CF) involved in recurrent pneumonia and pulmonary exacerbations. The type III secretion system (T3SS) is one of its main determinants of virulence and is associated with poor clinical progression and increased mortality. This study determined the relationship of clinical features of patients with CF and P. aeruginosa T3SS virulotypes. Materials and Methods: From January 2018 to March 2019, P. aeruginosa were isolated from sputum and/or oropharyngeal swabs. T3SS markers (exoS, exoU, exoT and exoY) were detected by PCR. Clinical severity according to Shwachman-Kulckycki score and spirometry data were associated with T3SS virulotypes. Results: A total of 49 patients had positive cultures for P. aeruginosa. T3SS virulence-related markers were detected as follows: exoS 97.9% (n=48), exoU 63.2% (n=31), exoT 95.9% (n=47) and exoY 97.9% (n=48). The prevalence of exoS+/exoU+ virulotype was higher than previously reported in CF settings, being detected in 61.2% of the evaluated isolates, present in 70% of intermittent infections and with a significantly higher frequency in cases of exacerba-tions. The presence of exoU in chronic infection was not associated with poor clinical results. In chronic infections, the exoS+/exoU? virulotype prevailed (77.8%) and was associated to worse clinical results according to the Shwachman-Kulckycki score and spirometric. Conclusion: Our findings revealed a high prevalence of the atypical exoS+ /exoU+ virulo-type among P. aeruginosa isolates from patients with CF, which was associated with intermittent infection and early clinical alterations, while the exoS+ /exoU? virulotype was associated with chronic infection and worse clinical results. Finally, the presented data highlight the relevance of T3SS virulence markers in the clinical progression and disease severity in CF patients.